SEBUAH STUDI PADA PROSES IDOLISASI TERHADAP IDOLA K-POP - Hanno Avila Pradata; Hartanti Hartanti; Darmawan Muttaqin (Perpustakaan Universitas Surabaya, 2018)
This research was based on k-pop music phenomenon which isbooming in Indonesian’s teenagers. Idolization process, the meaning towards the idol, support and positive impact on participant’s life are the the focus on this research. There are two participants and both are female teenagers. This research using qualitative methods and using interpretive phenomenological analysis as design of the research. Result shows that there was a stimulation to began the interest on a music from the family and this stimulation grows as reinforcement, given especially by mother’s side. There was also obstacles that came from father’s side which reacted by participants by crying and lying. The support which is received by participants was emotional support and instrumental support, which strengthen the idolization behaviour. In this idolization process, participants also received obstacles that came from outside the family, such as bullying that came from school’s mate because k-pop was thought as something feminime. Participant’s fanatism which came from idolization behaviour that was reinforced led to a condition which called internalization. This internalization condition came as sexual fantasies towards the idol and beliefs that idols as their boyfriends